THE ASSESSMENT OF PERSONALITY DIMENSIONS, TOBACCO SMOKING AND DEPRESSION AMONG TRETMENT- SEEKING MALE ALCOHOLICS - Mandić Gajić, Gordana; Eror, Aleksandar; Pješčić, Nataša; Dolić, Mirko; Joković, Danilo; Nikolić, Gordana (Vojnosanitetski pregled, 2020)
The co-occurrence of depression and tobacco smoking among treating alcoholics is frequent, but understudied. Some findings suggest that there are some shared aethiological factors, but a few clinical researches of personality dimensions among patients with these comorbidities were done. The personality dimensions, the pattern of cigarette use and depression and correlation of personality and depression among inpatient alcoholics were explored. Methods. The one hundred primary male inpatient alcoholics were consecutively recruited. The eigty six completed study and were compared with thirty male age matched healthy subjects. Semistructured clinical interview for sociodemographics, the pattern of cigarette and alcohol use and family history data was applied. According cut-off on Hamilton Depression Rrating Scale-HDRS (Hamilton, 1960) the alcoholics divided into depressive and non-depressive subgroups resulting in half of alcoholics in each subgroup. The Eysenck personality questionnaire- EPQ (Eysenck, 1975) was completed. Student t-test for differences and Pearson test for correlation were used. Results. There were no significant sociodemographic differences between groups. Alcoholics were more frequent smokers (86% vs. 50%). They didn’t started drinking earlier, but earlier started smoking, with higher daily cigarettes use than controls. Alcoholics had average mild depression degree after detoxification. The personality dimensions did not show differences between groups, except neuroticism. The neuroticism showed significantly higher level among alcoholics vs. controls (12.72±5.19 vs. 5.00±3.36) and among depressive vs. non-depressive alcoholics (15.07± 4.89 vs.10.37±4.40). The depression correlated only with neuroticism (r= 0.487, p<0.001). Conclusions. The majority of detoxified alcoholics were smokers, earlier started smoking with mild depression and higher neuroticism compared to controls. Our results suggest that the alcoholics with high neuroticism may experience higher depression and may require more intensive integrative treatment.